Characteristics of Water Absorption and Load-Bearing Resistance of Coconut Coir–Based Cocopot at Different Thicknesses - Muh Yamin; Farida Aryani; Mika Debora Br. Barus; Mujibu Rahman; Elisa Ginsel Popang; Edy Wibowo Kurniawan; Mamba’ul Ullum; Jamaluddin (Jurnal Loupe, 2025)
This study examines the characteristics of water absorption and load-bearing resistance of coconut coir–based cocopot with different thicknesses as an environmentally friendly planting medium. Cocopots were produced from a mixture of cocofiber, cocopeat, and latex adhesive with three thickness variations: 1.0 cm, 1.5 cm, and 2.0 cm. Water absorption was evaluated using a 5-minute immersion test, while load-bearing resistance was assessed by repeatedly dropping soil-filled cocopots from a height of 3 meters under a total load of 1,096 g. The results show a consistent trend indicating that increased thickness is associated with higher water absorption capacity and improved mechanical durability. Cocopots with a thickness of 2.0 cm exhibited the highest water absorption (90–91%) and the lowest damage level, with a Load-Bearing Resistance Index of 0.55–0.58%. In contrast, cocopots with a thickness of 1.0 cm showed the lowest performance. These findings suggest that thicker cocopots provide better functional characteristics for agricultural applications.